P786 The use and escalation of treatments in patients with inflammatory bowel disease; a 10 years follow-up of a Danish population-based inception cohort. (16th January 2018) - Lo, B; Vind, I; Bendtsen, F; Vester-Andersen, M; Burisch, J
Abstract: Background: The long-term treatment strategies and change between medications in Inflammatory bowel disease (IBD) in the age of biologics has not been well described. We aimed to characterise the treatment strategies in IBD in a well-defined population-based inception cohort of Crohn's disease (CD) and ulcerative colitis (UC) patients after 10 years of follow-up. Methods: All patients ( n = 513) diagnosed with CD, UC or IBD unclassified between January 1, 2003 and December 31, 2004 in a well-defined area were included. Clinical data regarding treatment and outcome were recorded and patient records linked with four national registries to ensure complete data capture and follow-up. Treatments were grouped into four treatment levels (TL): (1) 5-aminosalicylates (5-ASA) ± topical steroids, (2) oral steroids ± 5-ASA or topical steroids, (3) immunosuppressant (azathioprine or 6-mercaptopurine ± steroids and/or 5-ASA), (4) biologics (infliximab or adalimumab in combination with any of the above). Disease classification was made according to the Montreal classification. In a linear regression model, gender, age class, diagnostic delay, smoking behaviour, disease behaviour, location, and extent at diagnosis was used as independent variables. Results: A total of 213 CD and 300 UC patients were followed. TL over time is shown in Figure 1 and 2. Characteristics of patients' TL are shown in Table 1. In CD, only younger age at diagnosis was associated with the risk of escalating to TL 3 or 4 (OR (CI 95); A2: 0.7 (0.5, 0.98); A3: 0.5 (0.4, 0.8) [ref: A1]). In UC patients, former smoking (OR (CI95); 1.3 (1.0–1.6) [ref: never smoker]), and extent at diagnosis was significantly associated with the risk of escalating to TL 3 or 4 (OR (CI95); E2: 1.4 (1.2, 1.8), p < 0.001; E3: 1.4 (1.1, 1.7) [ref: E1]). Conclusions: After the first initial years after diagnosis, stability occurs regarding treatment levels of both CD and UC patients. Escalation to immunomodulators and biologics was more frequently necessary in CD, even after the initial years, compared with UC patients.